Effect of inoculants and additives on fractions of ruminal fermentation and in vitro degradation in sorghum silage (Sorghum sp) - Ramírez-Díaz, Roselia (Universidad Autónoma de Tamaulipas, 2020)
The action of inoculants and additives on the chemical composition and ruminal degradation of sorghum silage dry matter (DM) has already been reported. However, the effect that these have on the microbial activity and, therefore, on its potential for assimilation at the ruminal level is unknown. For that reason, the objective of this study was to evaluate the effect of the addition of inoculants and additives in silage of the entire plant of Sorghum sp. on fractions of ruminal fermentation and in vitro degradation. The experimental design was completely random, with 7 treatments (3 inoculants, 2 additives and a combination of inoculate with additive) and 21 repetitions per treatment. Different types of inoculants and additives were used in the process of sorghum silage: cheese whey, yogurt, phosphoric acid, Lactobacillus plantarum and mineral mixture. After 60 d of fermentation, dry matter (DM), hydrogen potential (Hp), crude protein (CP), in vitro dry matter degradation to 24 h (IVDMD), parameters of fermentation kinetics (Vmax= maximum volume L = lag phase, S = fermentation rate) and fractional volume (rapid fermentation = 0 h to 8 h, intermediate = 8 h to 24 h and slow = 24 h to 72 h) were quantified through the in vitro gas production technique. The results indicated that the inoculants and additives modified the chemical composition, the L parameters, Vmax, IVDMD and the rapid and intermediate fermentation fractions (P < 0.05). The use of cheese whey and L. plantarum as inoculants in sorghum silage reduced the loss of CP; and, overall, the use of inoculants and additives improved silage Hp; however, it decreased the use of rapid and intermediate fermentation fractions, modified the fermentation potential of the silage and provoked a negative effect on the IVDMD.